1993
DOI: 10.1073/pnas.90.24.11733
|View full text |Cite
|
Sign up to set email alerts
|

A translation-attenuating intraleader open reading frame is selected on coronavirus mRNAs during persistent infection.

Abstract: Short open reading frames within the 5' leader of some eukaryotic mRNAs are known to regulate the rate of translation initiation on the downstream open reading frame. By employing the polymerase chain reaction, we learned that the 5'-terminal 5 nt on the common leader sequence of bovine coronavirus subgenomic mRNAs were heterogeneous and hypervariable throughout early infection in cell culture and that as a persistent infection became established, termini giving rise to a common 33-nt intraleader open reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…It has been shown that the 5Ј UTRs of CoVs can influence the capacity of the virus to replicate in cells (46). Although the 5Ј UTR in the synthetic Bat-SCoV originated from SARS-CoV, the sole difference between Bat-SCoV, which was not capable of amplification in cell culture, and Bat-SRBD, which could be recovered, was the RBD derived from SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the 5Ј UTRs of CoVs can influence the capacity of the virus to replicate in cells (46). Although the 5Ј UTR in the synthetic Bat-SCoV originated from SARS-CoV, the sole difference between Bat-SCoV, which was not capable of amplification in cell culture, and Bat-SRBD, which could be recovered, was the RBD derived from SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…In the 5h leader of a number of eukaryotic mRNAs such short ORFs regulate the rate of translation of a downstream reading frame (Kozak, 1991). Although the functionality of the various arterivirus intraleader ORFs remains to be proven, it is interesting to note that similar intraleader ORFs can arise during persistent coronavirus infections (Hofmann et al, 1993 ;Chen & Baric, 1995).…”
Section: Genome Properties and Organizationmentioning
confidence: 99%
“…Although mechanisms underlying these phenomena are not completely understood, it has been shown that, in some cases, virus persistence is associated with the selection of viruses containing mutations that downregulate and/or inactivate a critical virus gene(s) (Borzakian et al, 1992;Hofmann et al, 1993). The IBDV genome harbours three open reading frames (ORFs) encoding: (i) the RdRp; (ii) a large polyprotein containing three domains, corresponding to the capsid protein precursor (pVP2), the viral protease (VP4) and a multitasking structural polypeptide (VP3); and (iii) a 17 kDa polypeptide, VP5, that accumulates at the cell membrane (Lombardo et al, 2000).…”
mentioning
confidence: 99%